Study Survey of Increasing Arabic Learning Due to Smartphones - Yakir, Julia; Jiao, Deng; Wang, Yuanyuan (Journal International of Lingua and Technology, 2022)
The Covid-19 pandemic has grown and spread in various countries, changing various areas of people's lives, especially in Indonesia, some time back. The purpose of this observation is to find out the use of smartphones for students of Junior High School madrasahwhen studying online. This observation is through a quantitative approach through the survey study method and selecting a random sample by establishing10 speakers who live in dormitories, namely Junior High School grade 7 students who have obtained questionnaire answers using google from. The research tool is adapted from several writings. The tool is made from 5 questions. The observation results found that there were seven people who had their own smartphones and three students used the smartphones of their parents, siblings and other people in online learning, while the time used to study through smartphones was between 5 to 6 hours. The students of Junior High School use smartphones are classified as a good category in learning because they can do and collect tasks well. So students discussed it with their friends, and all felt satisfied with using smartphones in online learning activities. Saran for the next researcher to use the variables of attitude and the impact of using smartphones for Junior High School students who have their own smartphones